An Analysis of Figurative Language in Toeti Heraty’s Poems - Sit Maisarah; Zulfadli A. Aziz; Chairina Nasir (Universitas Syiah Kuala, 2021)
The study aims to find out figurative languages used in Toeti Heraty’s Poems. The source is taken from Toeti Hearty’s poems. The research design used in this research is qualitative research with document analysis as a data collection technique. Abrams and Harpham’s theory (2005) used to analyze the data related to the types of figurative language. The results of the study showed that there are some types of figurative language used in Toeti Heraty’s poems such as simile, metaphor, hyperbole, alliteration, onomatopoeia, personification, symbol, repetition, and assonance. The result shows that the most figurative languages found in Toeti Heraty’s poems are personification. From the analysis that has been done, it was found 79 figurative languages contained in the four poems. The data found were personification consists of 19 data, repetition consists of 15 data, alliteration consists of 12 data, assonance consists of 9 data, metaphor consists of 7 data, hyperbole consists of 7 data, symbol consists of 7 data, simile consist of 3 data, and onomatopoeia consists 1 datum.